Research productivity across different ophthalmic subspecialties in the United States - Assaf Gershoni; Igor Vainer; Olga Reitblat; Francis B. Mimouni; Eitan Livny; Eytan Z. Blumenthal; Rita Ehrlich; Michael Mimouni (BMC Health Services Research, 2019)
Abstract Background The purpose of this study was to compare the h-index, and subsequently the research productivity, among different ophthalmic subspecialties in the United States. Methods A cohort of over 15,000 academic ophthalmologists residing in the United States (US) was identified out of the physician list of the American Academy of Ophthalmology. Of them, 1000 ophthalmologists with at least one publication were randomly retrieved, 100 in each of the following 10 subspecialties: cataract, cornea/external disease, glaucoma, medical retina, neuro-ophthalmology, pediatric ophthalmology, plastic/reconstructive ophthalmology, refractive surgery, retina/vitreous surgery and uveitis. Data collected included: number of published papers, h-index score, annual increase in h-index and the mean number of authors on each paper. Results The mean h-index amongst all subspecialties was 9.87 ± 13.90, and the mean average annual increase in h-index was 0.22 ± 0.21. The mean number of papers published was 37.20 ± 80.08 and the mean number of authors on each paper was 3.39 ± 0.84. Uveitis was the most prolific subspecialty in mean number of papers (74.78 ± 131.37), in mean h-index (16.69 ± 20.00) and in mean annual increase in h-index (0.35 ± 0.28). The least fertile subspecialty with regards to research was cataract with 11.06 ± 27.65 mean number of papers, a mean h-index of 3.89 ± 5.84, and a mean annual increase in h-index of 0.11 ± 0.11. Conclusions This study describes the research productivity in each ophthalmic subspecialty in the US, thus providing information on the research performance of each field and on the expected academic accomplishments within it.